Promoting Gender Equality in the Classroom: A Comparison between Methodologies used by Equal Education and the Department of Basic Education - Ovner, Louise (Department of Political Studies, 2020)
This thesis compares how the South African Government, specifically the Department of Basic Education and the NGO Equal Education to see how these organizations work to promote gender equality. The study will contribute to a systematic comparison of approaches between the Department of Basic Education and Equal Education. This thesis will contribute to the literature by emphasizing the importance of quality education, and not only providing access. The comparison is done by evaluating different projects, explicitly and implicit within the organizations through Elaine Unterhalter’s two approaches: the resourcist approach and the structuralist approach. The evaluation of these projects and interventions has helped determine to which extent gender equality is promoted in each organization, but also which approach is utilized by whom and if they are complementary or not. Currently the trends of the South African government point towards the use of mainly resourcist approaches, while Equal Education uses mainly structuralist approaches. However, the government plans to eventually create a change in the current social structure to address its usage of a mostly resourcist approach. These initiatives and projects has been defined resourcist or structuralist mainly due to their method of measure, which is a major driving force in these projects. At this time the approaches chosen by each organization affect gender equality at different depths and a hybrid between the two is a recommendation although there have been implementation issues in relation to some projects. The conclusion references the capabilities approach to determine what type of hybrid might be the most suitable for the promotion of gender equality.